2012
DOI: 10.1111/j.1471-0307.2012.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and biomass kinetics of activated sludge system treating dairy wastewater

Abstract: The performance and bio‐kinetic coefficients of the activated sludge process (ASP) treating synthesised dairy wastewater were evaluated in a lab‐scale setup. The step‐loading experiment showed that the chemical oxygen demand (COD) removal efficiency, in general, increased with increasing influent wastewater COD concentration from 180 to 1200 mg/L (correlation coefficient was 0.80). The COD removal efficiency ranged from almost 80–88.4% depending on the COD concentration of the influent wastewater. Also, it cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…These results indicated that higher salinity selection pressure stimulated the growth of halophilic nitrifier with low K s and μ max . K s is an important biological factor and determines the relative affinity of a microorganism towards its substrate 20 . The selected nitrifiers, with low K s when salinity was high, indicated strong affinity for the ammonium.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that higher salinity selection pressure stimulated the growth of halophilic nitrifier with low K s and μ max . K s is an important biological factor and determines the relative affinity of a microorganism towards its substrate 20 . The selected nitrifiers, with low K s when salinity was high, indicated strong affinity for the ammonium.…”
Section: Discussionmentioning
confidence: 99%
“…Q5 = COD/Ptot (5) 3 Results Table 4 summarizes the characteristics of dairy wastewater from the milk processing plant in Piatnica in 2016 and 2017. The factor affecting the efficiency of pollutant removal from wastewater is their composition.…”
Section: Q4 = Cod/ntot (4)mentioning
confidence: 99%
“…Quantity of dairy sewage is characterized by high seasonal variations (20% increase in spring and summer). Additional oscillations relate to the daily and hourly shift work dependent on the size, production profile, and shifts at milk processing plant [1][2][3][4][5][6][7][8][9][10][11][12][13]. Dairy wastewater is normally treated by physical, biological and chemical processes and the various possibilities are presented in fig.…”
Section: Introductionmentioning
confidence: 99%
“…Data on qualitative and quantitative characteristics of raw dairy sewage are relatively well-documented [4][5][6][7][8][9][10][11][12][13][14][15][16], but at the same time there are serious gaps in relation to the municipal sewage with a specific share of industrial (dairy) wastewater. For this reason, it is impossible to compare the results with literature data.…”
Section: Rates Of Parameters Change In Wastewater In Various Stages Omentioning
confidence: 99%
“…Quantity of dairy sewage is characterized by high seasonal variations (20% increase in spring and summer). Additional oscillations relate to the daily and hourly shift work dependent on the size, production profile, and shifts at milk processing plant [4][5][6][7][8][9][10][11][12]. Biological treatment of dairy wastewater is high-efficient due to the significant share of easily biodegradable substances [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%